Eastern tropical North Pacific coral radiocarbon reveals North Pacific Gyre Oscillation (NPGO) variability. (15th March 2017) - Rafter, Patrick A.; Sanchez, Sara C.; Ferguson, Julie; Carriquiry, Jose D.; Druffel, Ellen R.M.; Villaescusa, J.A.; Southon, John R.
Abstract: Fluctuations in oceanic circulation and upwelling associated with the North Pacific Gyre Oscillation (NPGO) are the largest source of salinity and nutrient concentration variability across the Pacific basin. Recent observations suggest NPGO-like variability is intensifying, but longer, "pre-instrumental" records are required to improve our understanding of NPGO amplitude and phase change. Here, using measurements of coral skeletal chemistry from San Benedicto Island in the Eastern Tropical North Pacific (ETNP), we assess this region's suitability for reconstructing NPGO behavior. We find that coral geochemical proxy measurements of ETNP salinity and dissolved inorganic carbon radiocarbon (Δ 14 C) content reflect NPGO-driven gyre circulation and regional coastal upwelling. These results provide the basis for reconstructing NPGO-related ocean conditions hundreds of years prior to the modern observational record. Highlights: Eastern tropical North Pacific coral radiocarbon reveals North Pacific Gyre Oscillation (NPGO) variability. Eastern Tropical North Pacific corals provide a means for reconstructing past ocean geochemistry. Large-scale climate oscillations have a predictable influence on some seawater geochemistry. New measurements of carbon and oxygen isotopes provide insight to past ocean upwelling and salinity. Results indicate that the NPGO is the dominant influence on local seawater salinity.